Design and production of an arch built of precast stackable components. (April 2019) - Enrique, Lluís; Schwartz, Joseph
Abstract: The CASTonCAST system deals with the design and production of concrete shell structures from precast stackable components. The investigation presented in this paper has the aim of testing the feasibility of this system at real scale. To do this, a thin free-standing funicular arch composed of twelve stackable components was built. The arch has a span of 5.15 m and its thickness varies between 8 cm at the supports and 4 cm at the key. The arch was post-tensioned by means of four steel cables of 6 mm diameter in order to obtain stiffness against point live loads. The results of this investigation show that the CASTonCAST system can easily be applied in real-scale construction. Problems related to tolerances in construction and concrete shrinkage were observed and must be addressed in future work.